Modeling the effect of temperature-control curtain on the thermal structure in a deep stratified reservoir. (1st November 2017) - He, Wei; Lian, Jijian; Yao, Ye; Wu, Mudan; Ma, Chao
Abstract: Temperature-control curtain (TCC) is an effective facility of selective withdrawal. Previous research has estimated the influence of TCC on the outflow temperature, but its effect on the thermal structure of a reservoir area is unknown, which is crucial to the reservoir ecology. For this purpose, taking the Sanbanxi Reservoir as a case study, a 2-D hydrodynamic and temperature model covering the whole reservoir was built and calibrated to simulate the flow and temperature fields under different TCC scenarios, and the change rules of thermal stability and outflow temperature are obtained. When the water-retaining proportion ( P r ) of bottom-TCC increases, the temperature difference between inflow and outflow monotonously decreases, while the thermal stability first increases and later decreases. The maximum thermal stability exists at P r  = 62.5%; it goes against water quality improvement and should be avoided in practice. A bottom-TCC with P r  > 80% is practical for deep reservoirs such as Sanbanxi Reservoir to decrease the temperature difference between inflow and outflow without the increase of thermal stability. In terms of top-TCC, as P r increases, the temperature difference between inflow and outflow monotonously increases and thermal stability decreases. The top-TCCs are recommended when a smaller thermal stability is more preferentially considered than outflow temperature, or a cool outflow in the summer is required for downstream coldwater fishes. In addition, the TCC cannot decrease or increase the outflow temperature all of the time throughout the whole year, and it primarily changes the phase and variation range of the outflow temperature. This study quantitatively estimates the potential effect of TCCs on the thermal structure and water environment management and provides a theoretical basis for the application of TCC. Graphical abstract: Highlights: A 2-D hydrodynamic and temperature model covering the whole reservoir was built. Seasonal hydrodynamic and temperature processes under TCCs were simulated. Influences of TCC on the thermal stability and outflow temperature were analyzed. The significances and application scopes of different TCCs were proposed.